Inovasi Desain Dan Teknologi Digital Pada Penjualan Produksi Gerabah UMKM Di Pagerjurang Bayat Klaten Menuju Go Internasional - Maria Atik Sunarti Ekowati; Sri Wening; Kristyana Dananti; Adrian Khrisnamurti Dorestia; Ian Nugroho Kristanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The PKM science and technology program has carried out the application of appropriate technology to the community for the 2023 Fiscal Year with the theme Design Innovation and Digital Technology in MSME Pottery Production Sales in Pagerjurang Bayat Klaten Towards Go International. The activities carried out were socialization of the importance of pottery innovation and management of sales using the internet/e-commerce, guiding the people of Pagerjurang Bayat village to manage the sale of pottery production. The implementation of the PkM community partnership is planned in 8 months, with the main output target in the form of E-Commerces for Pottery Sales, another expected impact of the IBM Science and Technology Program for the community is the emergence of public awareness in the sale of pottery production to go international, thus increasing the added value of the Pagerjurang community's income. freshman. Sales were severely constrained due to the Covid 19 pandemic, which had an impact on the economic decline of the Pagerjurang people. This is as a result of the decline in domestic and foreign tourists visiting the pottery tourism village in Pagerjurang Bayat. PkM partner collaboration was carried out with Carik and Kadus on the Bayat ravine pager. In order for the implementation of the IBM Science and Technology Program for the community to run more directed, the method used is in three stages, namely the planning stage (plan), the implementation stage (do) and the reflection stage (see). At the planning stage, the main activity carried out is introducing digital technology as a tool for selling pottery. In the implementation stage (do) the participants tested how to use the digital platform. While the reflection stage (see) the science and technology team reflects on the results of observations of the implementation of PkM activities. The results of the activity were then presented in front of the science and technology team and the science and technology participants for the community to get input from the science and technology team and participants to make further improvements